Melioidosis: Indian perspective - T Karuna; Sagar Khadanga; Dharmendra Dugar (International Journal of Medical Research and Review, 2014)
There has been an upsurge of melioidosis cases in India in recent past. Lack of awareness of this disease among the Indian clinicians and microbiologists is responsible for the wrong diagnosis as tuberculosis, scrub typhus, leptospirosis and brucellosis. Being one of the most potent emerging infections in India the clinicians and microbiologists should be suspicious of this organism in any suppurative lesions at multiple sites. Though B.pseudomallei has been most commonly reported in diabetic and immune compromised hosts, immunocompetency does not rule out its presence. All suspicious samples should be incubated for 5-7 days to isolate the organism. They should be treated for 10-14 days as Intensive therapy in the hospital with sensitive intravenous antibiotic followed by 3-6 months of oral therapy with Cotrimoxazole for complete eradication.